2021
DOI: 10.1111/ijfs.15126
|View full text |Cite
|
Sign up to set email alerts
|

Flavour characteristics of rice wine fermented with mixed starter by moulds and yeast strains

Abstract: Summary Mixed starter of pure mould and yeast was designed to circument the problem of flavour characteristics in rice wine. The result underlined that the mixed starter (Q7) made by simultaneous inoculation of Rhizopus oryzae, Saccharomyces cerevisiae, Wickerhamomyces anomalus and Candida glabrata had the highest contents of α‐amylase (8.02 ± 0.96 U/g) and sensory scoring (92.05 ± 2.24), presenting relatively strong flower‐aroma, wine‐aroma, Qu‐aroma and rice‐aroma. Meanwhile, the total concentration of flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Acyl‐CoA produced by S. cerevisiae is a precursor for the formation of ethyl esters by enzymatic condensation of organic acids and ethanol via anabolism during fermentation (Pires et al., 2014). Other aroma compounds found in the makgeolli samples were consistent with the literature, as benzaldehyde (almond flavor) (Chen, Wang, et al., 2021), 1‐octanol, 2‐octanol (earthy/must aroma), ethyl acetate (fruity aroma) (Chen, Ren, et al., 2021), and phenylethyl alcohol (rose and floral aroma) (Yu et al., 2019) were previously identified in the literature and also present in this study. Table 3 shows the volatile compounds identified from the SPME–GC–MS.…”
Section: Resultssupporting
confidence: 89%
“…Acyl‐CoA produced by S. cerevisiae is a precursor for the formation of ethyl esters by enzymatic condensation of organic acids and ethanol via anabolism during fermentation (Pires et al., 2014). Other aroma compounds found in the makgeolli samples were consistent with the literature, as benzaldehyde (almond flavor) (Chen, Wang, et al., 2021), 1‐octanol, 2‐octanol (earthy/must aroma), ethyl acetate (fruity aroma) (Chen, Ren, et al., 2021), and phenylethyl alcohol (rose and floral aroma) (Yu et al., 2019) were previously identified in the literature and also present in this study. Table 3 shows the volatile compounds identified from the SPME–GC–MS.…”
Section: Resultssupporting
confidence: 89%
“…Saccharomyces cerevisiae, a conventional choice in the alcoholic wine industry, is favored for its exceptional fermentation capabilities and robust tolerance [4,5]. Aroma stands as a paramount factor in gauging both the quality of fruit wine and its reception among consumers.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional production of SFGR relies on microorganisms present in the rice material and its surrounding environment, posing safety risks and leading to inconsistent flavour quality (Zhao et al, 2023). Currently, there is an increasing interest in intentionally adding probiotics as fermentation starters to Chinese traditional rice fermented products in order to enhance their flavour and overall quality (Xiang et al, 2019;Chen et al, 2021c). For example, Chen et al (2021c) investigated the artificial addition of Wickerhamomyces anomalus and Candida glabrata as starters for fermenting Chinese rice wine.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is an increasing interest in intentionally adding probiotics as fermentation starters to Chinese traditional rice fermented products in order to enhance their flavour and overall quality (Xiang et al, 2019;Chen et al, 2021c). For example, Chen et al (2021c) investigated the artificial addition of Wickerhamomyces anomalus and Candida glabrata as starters for fermenting Chinese rice wine. They observed that these new starters led to an improved floral aroma of the rice wine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation